Comprehensive analysis of metabolites produced by co-cultivation of Bifidobacterium breve MCC1274 with human iPS-derived intestinal epithelial cells - Sen, Akira; Nishimura, Tatsuki; Yoshimoto, Shin; Yoshida, Keisuke; Gotoh, Aina; Katoh, Toshihiko; Yoneda, Yasuko; Hashimoto, Toyoyuki; Xiao, Jin-Zhong; Katayama, Takane; Odamaki, Toshitaka (Frontiers in Microbiology, 2023)
Examining how host cells affect metabolic behaviors of probiotics is pivotal to better understand the mechanisms underlying the probiotic efficacy in vivo. However, studies to elucidate the interaction between probiotics and host cells, such as intestinal epithelial cells, remain limited. Therefore, in this study, we performed a comprehensive metabolome analysis of a co-culture containing Bifidobacterium breve MCC1274 and induced pluripotent stem cells (iPS)-derived small intestinal-like cells. In the co-culture, we observed a significant increase in several amino acid metabolites, including indole-3-lactic acid (ILA) and phenyllactic acid (PLA). In accordance with the metabolic shift, the expression of genes involved in ILA synthesis, such as transaminase and tryptophan synthesis-related genes, was also elevated in B. breve MCC1274 cells. ILA production was enhanced in the presence of purines, which were possibly produced by intestinal epithelial cells (IECs). These findings suggest a synergistic action of probiotics and IECs, which may represent a molecular basis of host-probiotic interaction in vivo.